1983
DOI: 10.1159/000287765
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Alternative Practitioner and His Patient A Review

Abstract: The present paper reviews the empirical studies which have dealt with the therapeutic relationship between the alternative practitioner and his patient. These are based mainly on interviews with patients of nonmedical practitioners of alternative medicine which have been carried out in a few industrialized countries. When evaluating the results of these investigations, one has to consider a number of methodological pitfalls. Nevertheless, there is sufficient evidence for the statement that an asset of the alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…GPs are generally perceived to be more "formal" than complementary practitioners are [30], but CM practitioners tend to give more time for consultation [31] and may enjoy the advantage of the "power of touch"-compared to GPs, CM practitioners seem to undertake physical examination more frequently. Furnham and Kirkcaldy (1996) [6] reported that GP practice was less satisfied by CM patients.…”
Section: Perceptions Of Physiciansmentioning
confidence: 99%
“…GPs are generally perceived to be more "formal" than complementary practitioners are [30], but CM practitioners tend to give more time for consultation [31] and may enjoy the advantage of the "power of touch"-compared to GPs, CM practitioners seem to undertake physical examination more frequently. Furnham and Kirkcaldy (1996) [6] reported that GP practice was less satisfied by CM patients.…”
Section: Perceptions Of Physiciansmentioning
confidence: 99%
“…We can choose to view those who seek alternative care as people who have a greater sensitivity towards their body, are confident that they can make a difference in improving their health, and have a greater desire for long-term health. In general, clients who value an egalitarian therapeutic relationship (Hewer, 1983), aspire towards a greater degree of participation in health care decisions and the wellness process, and are less likely to passively accede to the treatments prescribed by their health care provider.…”
Section: Naturopathy and Professional Counseling As Partnersmentioning
confidence: 99%
“…For example, blame is often put on the sprawling bureaucracies that modern health-care systems have become, with patients unhappy at feeling 'processed' rather than 'treated' (e.g. Hewer 1983). However, depersonalization sometimes results from less innocent factors.…”
Section: The Behaviour Of Hospital Staffmentioning
confidence: 99%